STRATEGI PENGEMBANGAN PENDIDIKAN AKHLAK PERSPEKTIF KH. HASYIM ASY’ARI DALAM KITAB ADABUL ‘ALIM WAL MUTA’ALLIM - Ramli, Natasyya Nabilla Musalwa; Ekawati, Ekawati (Universitas Pahlawan Tuanku Tambusai, 2025)
Moral education is a crucial foundation in the Islamic education system, aiming to develop noble, moral, and responsible individuals. This study aims to identify challenges and formulate effective strategies for developing moral education in the modern era, drawing on the thoughts of KH. Hasyim Asy'ari in his book Adab al-'Alim wa al-Muta'allim. This study employed library research with a qualitative descriptive approach. The results indicate that strategies for developing moral education can be implemented through role models, habituation, advice, and strengthening the roles of teachers and families, as well as the wise use of media. KH. Hasyim Asy'ari's thoughts emphasize that moral education must be instilled through respect for knowledge, educators, and the learning process. By integrating moral values into the education system as a whole, it is hoped that students can grow into civilized individuals with Islamic personalities.